(untitled) (American & British Studies Annual, 2019)
Discussions on the nature of time represent a significant theme in Jeanette Winterson’s novels. The author repeatedly challenges the generally accepted notions of time as chronological and measurable by the clock and she offers alternative perceptions of temporal reality based primarily on subjective experience. The aim of this paper is to examine this alternative approach to time and discuss the ways in which the categories of the past, the present and the future are deconstructed in Winterson’s work, particularly in the novels The Passion, Sexing the Cherry, The PowerBook and The Stone Gods. This article argues that Winterson’s stories encourage the reader to withdraw from everyday distractions and turn inwards towards his/her inner self in order to see and understand these new layers of time. Moreover, Winterson repeatedly portrays love as an all-powerful force defying spatial and temporal boundaries and thus allowing the emergence of an alternative, timeless reality bound by no rules or limitations. In Winterson’s novels, it is love that determines the course of time rather than the clock. The paper discusses this special significance of love in the novels and examines Winterson’s unconventional conception of the world, one in which the mind is freed from social expectations and where time is meaningless, since different temporal layers can operate simultaneously.